An Ultra-Low Free-Formaldehyde Durable Flame-Retarding Finishing for Ramie Fabric - Huaqing Wang (Journal of Natural Fibers, 2019)
An ultra-low free-formaldehyde durable flame retardant, called Argafun RFR, was applied to ramie fabric. The flame-retarding finishing procedure was optimized and flame-retardant-treated ramie fabrics was analyzed. An assessment of the thermal and flammability properties for these ramie fabrics showed that the thermal and thermal-oxidative stability, flame retardancy, and char formation were significantly enhanced after flame-retarding finishing, which was mostly attributed to the barrier effect of intumescent network structure formed from the dehydration and carbonization of cellulose accelerated by RFR Argafun. These ramie fabrics had good durability to washing, whiteness, breaking strength, and ultra-low free-formaldehyde.